Isotopic Analysis of Uranium and Plutonium at Ultra Trace Levels Using Thermal Ionization Mass Spectrometry with Simultaneous Measurements - Park, Jong-Ho; Jeong, Kahee; Song, Kyuseok (Asian Journal of Chemistry, 2013)
A thermal ionization mass spectrometer was utilized to determine the isotopic ratios of uranium and plutonium in standard materials. Because the total amounts of uranium and plutonium for measurement were present at pg levels, the peak jumping method, which is normally used to vary the magnetic field to detect each corresponding isotope one by one, was not an appropriate method for detection. A simultaneous measurement of the isotopes of interest that adopted a multiple ion counter system was used instead to ensure high levels of analytical precision and accuracy. A correction technique using reference measurements was applied to correct mass biases and background contributions. The measurements of the target materials with the corresponding certified values, which showed that the thermal ionization mass spectrometry measurement of uranium and plutonium with the simultaneous detection method is suitable for the analysis of unknown environmental samples with high accuracy and precision.